Serum of transthyretin as a treatment-responsive biomarker for schizophrenia - Nakagawa, Nobuaki; Yao, Hiroshi; Nakahara, Tatsuo; Inomata, Shinsaku; Hashimoto, Kijiro; Kuroki, Toshihide (Brain and nerve = Shinkei kenkyū no shinpo, 2013)
We investigated the changes in protein profiles of treatment responsive biomarkers in three subjects with first-onset schizophrenia using the surface enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) technology. Our results showed that eight protein peaks were down-regulated or up-regulated during the acute phase, and returned toward the control values during the recovery phase. In particular, a 13,761Da protein peak was markedly down-regulated during the acute phase, and returned during the recovery phase. This protein was identified as unmodified transthyretin using two-dimensional electrophoresis followed by peptide mass fingerprinting based on matrix assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). However, we failed to show transthyretin changes with the treatment using enzyme-linked immunosorbent assay (ELISA) and two-dimensional electrophoresis. The distinction between unmodified and modified subtypes of transthyretin was difficult with these methods because of similar molecular weights and isoelectric points in these subtypes. The present study showed that the application of SELDI-TOF-MS technology has higher precision for the distinction of detailed molecular weight than conventional proteomics techniques such as ELISA and two-dimensional electrophoresis. The dynamic changes in transthyretin have been reported to be associated with acute-psychosis condition; the present study suggested that unmodified transthyretin has the potential to be a treatment responsive biomarker for schizophrenia.